Sources of psychological stress among physically disabled athletes - zioche, ahmed; athmani, ABDELKADER (sports creativity, 2025)
Psychological stress at work, in training, or in social adaptation is an important aspect of life's pressures. It is a psychological phenomenon, like anxiety, aggression, and others, that cannot be denied. Rather, it must be addressed by specialists to help the individual adapt to his work, train for something, or cope with a situation, leading to social adaptation, raising the level, increasing productivity and quality at work, and thus developing and advancing society. According to researchers and specialists in adapted physical activity, it is one of the most stressful fields, due to the abundance of stressful stimuli in the sports environment. Some of these stimuli are due to the personality of the coach, which determines his ability to adapt to the rapid and significant changes in the field of training the physically disabled, and to the decisions, regulations, and laws that govern or restrict his work concerning the physically disabled category. Others are due to the social environment and the sports audience in which the sports team lives. While addressing the phenomenon of work-related stress in general is important, it is even more crucial to address the stress experienced by physically disabled individuals during their participation in sports teams, both in training and official competitions. This is due to the serious consequences of prolonged psychological stress, which can ultimately lead to psychological burnout. Burnout is characterized by pessimism, apathy, low motivation, a loss of creativity at work, and a mechanical approach to tasks. In other words, it lacks the emotional connection that is a fundamental pillar of individual adjustment, leading to exhaustion, decreased efficiency, and increased negative impacts on their lives (see Laila Othman Ibrahim Othman, 1987, p. 12). Therefore, we must identify the main sources of psychological stress experienced by physically disabled individuals in sports teams and then find the best solutions to address them. This will enable physically disabled individuals to achieve social adjustment and emotional integration within the sports team, ultimately facilitating their adaptation to the sport and leading to the desired results.